Influence of Hydrothermal Aging under Two Typical Adhesives on the Failure of BFRP Single Lap Joint - Yisa Fan (Polymers, 2022)
Facing increasingly serious resource crises, energy conservation is becoming the development trend of various delivery vehicles, and lightweight is an important way to achieve energy conservation. In this paper, the basalt fiber-reinforced resin composite material (BFRP) was selected to study the effect of its bonding structure, and it was used to make BFRP-BFRP joints. Two adhesives, Araldite®2012 and Araldite®2015, were used to make single-lap joints and dumbbell-shaped specimens. Aging environments of 80 °C/95% RH and 80 °C/pure water were used for the 0-day (unageing), 10-day, 20-day, and 30-day aging tests, respectively. According to Fick’s second law, the moisture absorption change model of two adhesives was established, and it was found that the water absorption process could be divided into two stages, which explains the precipitation of water molecules and the reaction of water molecules with functional groups. The maximum average failure load and load-displacement curves under different environments and different joints were obtained by using the electronic universal tensile machine, and the exposure time was more important than the effect of humidity. At the same time, the change law of failure strength and ductility were analyzed. The change of Tg (Glass transition temperature) was analyzed by differential scanning calorimetry (DSC) equipment, and the results showed that molecular chain rupture was the reason for the decrease of Tg. It could be seen from the joint failure mode distribution that Araldite®2012 adhesive was easily affected by the environment, and the joint of Araldite®2015 adhesive was affected by the combined effect of the adhesive and BFRP.